Further Investigations at 34-38 Newnham Road, Cambridge - Timberlake, Simon; Webb, David (Cambridge Archaeological Unit, Department of Archaeology, University of Cambridge, 2006)
An on-going watching brief of building excavations beneath an area of new wall being undertaken at nos. 34-38 Newnham Road during February 2006 provided further evidence of the nature and extent of a medieval pond in the backyard, whilst at the level of a mid-late 18th century ‘cellar’ (beneath no.36a) building excavations had exposed the foundations for what were in all probability a series of 17th century tenements fronting Newnham Road (Newnham High Street). An archaeological test pit revealed a still earlier floor surface underlying the levelling/make-up layers for these brick buildings which might relate to a 16th century or earlier timbered house. Below this a layer of garden soil containing sherds of 15th century coarseware suggested a still earlier phase of intensive backyard cultivation, perhaps associated with medieval dwellings on Maltings Lane (Froshlake Way) or Elde Newenham Weye (Newnham Road). Behind this area of garden, the large pond (up to 2.5 m deep) may originally have been excavated as a gravel pit, then flooded and used as a fishpond, perhaps associated with the nearby Mortimer’s (Newnham) Mill, or the fishponds adjacent to the mill dam leased by St. John’s Hospital. Evidence for some sort of sophisticated water management here has turned up in the form of (lain?) sections of probable 15th century (Ely Ware) ceramic water pipe – a potentially important find. In addition, some well preserved but probably broken and therefore discarded fragments of a ?15th century leather shoe were recovered from the base of the pond.